Basic guide to system safety - Vincoli, Jeffrey W. (Hoboken, New Jersey : Wiley, 2014)
'This book provides guidance on including prevention through design concepts within an occupational safety and health management system. Through the application of these concepts, decisions pertaining to occupational hazards and risks can be incorporated into the process of design and redesign of work premises, tools, equipment, machinery, substances, and work processes including their construction, manufacture, use, maintenance, and ultimate disposal or reuse. These techniques provide guidance for a life-cycle assessment and design model that balances environmental and occupational safety and health goals over the life span of a facility, process, or product.The new edition is expanded to include primer information on the use of safety assurance techniques in design and construction'--Provided by publisher.
14. HAZOP and What-If Analyses -- Introduction -- Background -- Definitions -- Objectives -- Team Members -- Reference Data Requirements -- The Concept of'Nodes' -- Conducting the What-If Analysis -- What-If Analysis Steps -- The What-If Analysis Worksheet -- Conducting The HAZOP Study -- The HAZOP Worksheet -- The Analysis Report -- Summary -- 15. Special Use Analysis Techniques -- Introduction -- Sneak Circuit Analysis -- Types and Causes of Sneaks -- SCA Input Requirements -- Advantages and Disadvantages of the SCA -- Software Hazard Analysis -- Types of SWHA Techniques.
Includes index.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Industrial safety; System safety; Occupational Health; Safety; Safety Management; Electronic books; Electronic books